Building a Primary Prevention Ecosystem in the United States: A Model for Transforming How Society Supports Children and Families. - Jones, Jennifer A.; Watson, Erin R.; Sutton, Kiersten L. (Families in Society: Journal of Contemporary Social Services, 2026)
As disparities in health and well-being outcomes continue to widen in the United States, despite good-willed investments in programs and services, a revolutionary shift in how we support families before they are in crisis is necessary to ensure they have what they need to be happy, healthy, and economically secure. To address these challenges, Prevent Child Abuse America developed a theory of change to address the root causes of child abuse and neglect, and balance the use of programs and systemic interventions to bring about a Primary Prevention Ecosystem to advance equitable outcomes for all children, youth, and families. As this Primary Prevention Ecosystem is realized in communities across the United States, there will be less need for the formal child welfare system as it exists today. This article describes the theory of change, the participatory methods used to develop it, and its implication for use within the broader primary prevention field.